2018
DOI: 10.2174/1381612823666170918121556
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analyses for Continuous Evaluation of Pharmacotherapy: A Proof of Principle with Doxapram in Preterm Infants

Abstract: Using high-frequency monitoring data, we showed the detailed effects over time of pharmacotherapy. We could objectively determine the respiratory condition and the effects of doxapram treatment in preterm infants. This type of analysis might help to develop individualized drug treatments with tailored dose adjustments based on a closed-loop algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Two retrospective studies concluded that doxapram therapy may avoid mechanical ventilation (Prins et al, 2013;Flint et al, 2017a). In our earlier studies, doxapram therapy had a positive effect on the SpO 2 , the applied FiO 2 (Flint et al, 2017b), the oxygen need (SpO 2 /FiO 2 ratio), and hypoxia (cumulative oxygen shortage under the 89% limit) (Poppe et al, 2019). The present study is the first in which doxapram therapy effects were continuously evaluated in individual patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Two retrospective studies concluded that doxapram therapy may avoid mechanical ventilation (Prins et al, 2013;Flint et al, 2017a). In our earlier studies, doxapram therapy had a positive effect on the SpO 2 , the applied FiO 2 (Flint et al, 2017b), the oxygen need (SpO 2 /FiO 2 ratio), and hypoxia (cumulative oxygen shortage under the 89% limit) (Poppe et al, 2019). The present study is the first in which doxapram therapy effects were continuously evaluated in individual patients.…”
Section: Discussionmentioning
confidence: 57%
“…This type of alarm interpretation by clinicians has been found inconsistent when compared to objectively analyzed monitor data (Brockmann et al, 2013). Continuous data on arterial oxygen saturation (SpO 2 ) and administered fraction of inspired oxygen (FiO 2 ) recently showed potential in assessing the PD of doxapram (Flint et al, 2017b;Poppe et al, 2019). Especially composite parameters that reflect oxygen need (SpO 2 /FiO 2 ratio) and hypoxia (oxygen shortage under the 89% limit) were found strong indicators of therapy effect (Poppe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Second, formulations often contain excipients that might be harmful or toxic to neonates, such as benzyl alcohol and propylene glycol [7]. For example, the commercially available preparation of doxapram (Dopram®) in the USA is contraindicated for use in neonates as it contains benzyl alcohol, which might be harmful to infants, while a benzyl alcohol-free formulation in Europe enables a wider use to treat apnea of prematurity [8]. Third, data on compatibility of repurposed drugs are needed.…”
Section: Repurposing Of Drugsmentioning
confidence: 99%
“…Cefazolin is a first‐generation cephalosporin beta‐lactam antibiotic used for treatment of sepsis or life‐threatening infections (McWhinney et al, ), where adequate individual dosing may be lifesaving. Doxapram has not been investigated sufficiently in children, despite its frequent and promising use in neonatal intensive care for treatment of apnea of prematurity (Flint et al, , Flint et al, ; Pacifici, ; Prins et al, ).…”
Section: Introductionmentioning
confidence: 99%